2020
DOI: 10.1101/2020.01.17.910869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of emotions based on functional connectivity patterns of the human brain

Abstract: Neurophysiological and psychological models posit that emotions depend on connections across widespread corticolimbic circuits. While previous studies using pattern recognition on neuroimaging data have shown differences between various discrete emotions in brain activity patterns, less is known about the differences in functional connectivity. Thus, we employed multivariate pattern analysis on functional magnetic resonance imaging data (i) to develop a pipeline for applying pattern recognition in functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Multivariate pattern detection approaches are particularly promising towards this end. A very recent preprint suggests that different induced primary emotions can be decoded from brain-wide functional connectivity data (in line with primary emotion theory) but that a distributed set of withinand between-network connections support each emotional state (contradicting clear localizationist views) 72 . It might very well be the case that emotions are both integrated and segregated at the same time.…”
Section: Discussionmentioning
confidence: 97%
“…Multivariate pattern detection approaches are particularly promising towards this end. A very recent preprint suggests that different induced primary emotions can be decoded from brain-wide functional connectivity data (in line with primary emotion theory) but that a distributed set of withinand between-network connections support each emotional state (contradicting clear localizationist views) 72 . It might very well be the case that emotions are both integrated and segregated at the same time.…”
Section: Discussionmentioning
confidence: 97%
“…For example, a proximal threat can activate periaqueductal gray matter and central nuclei of the amygdala [ 83 ], but a distant threat activates the VMPFC. A recent study that used multivariate pattern classification showed that distinct subnetworks representing different emotions are observed in the DMN [ 84 ].…”
Section: Default Mode Networkmentioning
confidence: 99%
“…The pattern similarity of the unthresholded predictive weights within the MPFC between the two models was low, r = 0.064. In addition to the default mode and limbic network regions, many voxels within the somatomotor and ventral and dorsal attention networks were among the important features of the models, suggesting that the information about the levels of self-relevance and valence involves many brain regions distributed across multiple brain systems 78,[86][87][88][89][90] .…”
Section: Multivariate Pattern-based Predictive Models Of Self-relevance and Valencementioning
confidence: 99%